2011
DOI: 10.1016/j.aap.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Distance between speed humps and pedestrian crossings: Does it matter?

Abstract: Speed humps are a common physical measure installed at pedestrian crossings to reduce vehicle speeds therefore improve the safety and mobility of pedestrians at the crossing. The aim of this study was to determine whether variations in distance between speed humps and pedestrian crossings contribute differently to the safety and mobility of pedestrians and cyclists, especially children and the elderly, and if so, how. Three sites in Sweden were studied, where vehicle speed measurements and video filming at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Speed humps, like other speed calming measures, have advantages and disadvantages (noise, vibration, pollution). Therefore, the researchers [13,14,15,16] still continue their studies related to speed humps seeking to determine the most effective parameters, spacing, etc.…”
Section: Efficiency Of Speed Humpsmentioning
confidence: 99%
“…Speed humps, like other speed calming measures, have advantages and disadvantages (noise, vibration, pollution). Therefore, the researchers [13,14,15,16] still continue their studies related to speed humps seeking to determine the most effective parameters, spacing, etc.…”
Section: Efficiency Of Speed Humpsmentioning
confidence: 99%
“…A synthesis of best practice destrian crossing. (Johansson, Rosander, & Leden, 2011). We have still included the site since speeds were very similar to those in Malmö, and the behavioral studies were useful.…”
Section: Test Sites In Swedenmentioning
confidence: 99%
“…Similarly, drivers' and pedestrians' behavior at pedestrian crossings has been extensively researched, see, e.g., Johansson (2004) and Várhelyi (1998). However, the influence of the distance between a speed hump and a pedestrian crossing was not a focus of any study until 2011, when it was concluded that the optimal distance from such a device to the crosswalk is about 10 m if the speed limit is 30 km/h or lower (Johansson, Rosander & Leden, 2011). Swedish guidelines still do not discuss the distance between the speed hump and the crossing explicitly.…”
Section: Children and Traffic -An Introductionmentioning
confidence: 99%
“…Based on those studies mentioned above, we cannot draw firm conclusions about the spatial effectiveness of the devices because of the following. (1) Vehicle speeds were usually recorded at few spots, such as at 2 or 3 points [4,10,11] along the road segment; therefore, we have limited information of how vehicle speeds change along the entire road segment. (2) Speed indicators used in these researches are collective indexes; some bias may be induced due to loss of information of the data aggregation process, that is, the socalled ecological fallacy.…”
Section: Introductionmentioning
confidence: 99%